The Environmental Criteria as a Strategy to Adapt Climate Changes in Iraq - Abed Hassan, Susan (International Journal of Engineering and Technology, 2018)
The Climate change appears obviously in the world, especially in hot climate regions like Iraq, because of their proximity to the equator and the geographical desert nature, which requires strategies to adapt climate change in effective ways. One of the most prominent of these strategies is the implemented of environmental criteria for buildings, to minimize the climate change effect. This research problem is that no obvious perception for the obstacles and the assistant methods for adopted environmental criteria as a strategy to adapt climate changes in Iraq". To solve this problem a questionnaire were designed about the main research indicators and delivered to the building industry practitioners. Statistical analysis were used to calculate the results, using IBM SPSS V23 software, the results find that the obstacles of application environmental criteria are economic, social, technical, and legislation. And the assistant method includes developing technical aspects, enabling human resources, cooperation with responsible authorities and decision-makers, and community awareness. The results indicated many recommendations for the local government, community organizations and the workers to implement environmental criteria as a strategy to adapted climate change in Iraq.Â Â